2019
DOI: 10.1186/s12879-019-4163-4
|View full text |Cite
|
Sign up to set email alerts
|

The inference of HIV-1 transmission direction between HIV-1 positive couples based on the sequences of HIV-1 quasi-species

Abstract: Background To infer transmission direction of a HIV transmission chain is helpful not only in legal jurisdiction but also in precise intervention to prevent HIV spread. Recently, the direction of transmission is inferred by whether paraphyletic-monophyletic (PM) or a combination of paraphyletic and polyphyletic (PP) topologies is observed or not between the sequences of source and recipient in the phylogenetic tree. However, paraphyly between them often declines over time and may disappear between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…There is a noticeable drop in discriminatory power when our models only include readily obtainable information, and thus, our results confirm that inferences about directionality entail considerable uncertainty in the absence of key epidemiological information ( 37 ). Moreover, because the stage of the transmitting partner’s infection is likely to influence the topology class of the phylogenetic tree, which in turn, influences the probability of correctly identifying the transmitting partner, chronic-stage transmitters who are more likely to exhibit PM topologies are thus more likely to be correctly identified ( 8 ).…”
Section: Discussionsupporting
confidence: 72%
“…There is a noticeable drop in discriminatory power when our models only include readily obtainable information, and thus, our results confirm that inferences about directionality entail considerable uncertainty in the absence of key epidemiological information ( 37 ). Moreover, because the stage of the transmitting partner’s infection is likely to influence the topology class of the phylogenetic tree, which in turn, influences the probability of correctly identifying the transmitting partner, chronic-stage transmitters who are more likely to exhibit PM topologies are thus more likely to be correctly identified ( 8 ).…”
Section: Discussionsupporting
confidence: 72%
“…Indeed, two variables that are not typically known and are not included under our real-life conditions model-the recency of the transmitter's infection at the time of transmission and the time from transmission-have been shown to influence the topology class (8,9), which in turn influences the chance of correctly identifying the transmitting partner. In the absence of such data, our results confirm that inferences about directionality can entail considerable uncertainty (31). Nonetheless, our results shed light into the possible reasons for variability between studies.…”
Section: Discussionsupporting
confidence: 77%
“…Research has shown that unhealthy lifestyles including smoking, lack of physical exercise and substance abuse put PLWHA at an increased rate of disease progression, opportunistic infections and chronic obstructive pulmonary diseases [6][7][8][9]. In additional, risky sexual behaviors among HIV positive people put their partners at risk for HIV infection and other sexually transmitted infections [10][11][12]. Moreover, the success of the "treatment as prevention" model also requires interventions that provide PLWHA the necessary skills to develop and sustain health-promoting behaviors including healthy sexual behaviors [13,14].…”
Section: Introductionmentioning
confidence: 99%